Applying Team Work in University - Milkov, Luchiyan (Research Papers, 2006)
Teamwork has been established in University studies during the last decades as a very efficient form. Developing the social skills in students has become more imperative as well as to participate in taking joint decisions in accomplishing collective goals.Teamwork is a modern pedagogy novelty. It has got science status established in theoretic and practice-enclosed didactic researches. Its technology in the process of education brings out various didactic techniques and models. They aim to identify the didactics relations in a new construction, based on more productive knit between students and students and lecturers. That construction helps achieving higher individual success. Team organization of studies is a bringer of the new teaching paradigm – personal life and action within plural society.Interaction and common support between subjects during the learning process are the most effective forms of teamwork in university studies. By using them students manage current learning strategies and lecturers explore the opportunities of implementing modern teaching models.